2016
DOI: 10.1590/1518-8345.0305.2741
|View full text |Cite
|
Sign up to set email alerts
|

Newborns' temperature submitted to radiant heat and to the Top Maternal device at birth

Abstract: Objective: to compare the axillar temperatures of newborns that are put immediately after birth in skin-to-skin contact under the Top Maternal device, as compared to those in a radiant heat crib. Methods: comparatives observational study of the case-control type about temperature of 60 babies born at the Obstetric Center and Normal Delivery Center of a public hospital of the municipality of Sao Paulo, being them: 29 receiving assistance in heated crib and 31 in skin-to skin contact, shielded by a cotton tissue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 12 publications
0
9
0
2
Order By: Relevance
“…Porém, em alguns depoimentos, observou-se que o primeiro banho realizado no RN, a equipe de enfermagem leva em consideração o que é preconizado pela OMS (12) , no tocante à realização do primeiro banho após 6h de vida da criança. A exceção ficará para os casos em que o RN está banhado em mecônio ou é filho de mulher portadora do vírus da hepatite B, herpes vírus ou HIV, com o objetivo de remover resíduos de sangue materno, minimizando a exposição do Rn e da equipe a esses agentes patológicos (31,32) .…”
Section: Resultsunclassified
“…Porém, em alguns depoimentos, observou-se que o primeiro banho realizado no RN, a equipe de enfermagem leva em consideração o que é preconizado pela OMS (12) , no tocante à realização do primeiro banho após 6h de vida da criança. A exceção ficará para os casos em que o RN está banhado em mecônio ou é filho de mulher portadora do vírus da hepatite B, herpes vírus ou HIV, com o objetivo de remover resíduos de sangue materno, minimizando a exposição do Rn e da equipe a esses agentes patológicos (31,32) .…”
Section: Resultsunclassified
“…The construction of instruments in several research areas has become common and has great influence on decisions about excessive humidity and friction with the skin, favoring cellular integrity and maintenance of the protective function (24)(25) . The towel should be close to the bathing area and easily accessible so that the baby is not exposed to temperature variations (26) .…”
Section: Discussionmentioning
confidence: 99%
“…With similar findings, a randomized clinical trial (conducted in Canada) showed that the immersion bath, with a water temperature range of 37.8°C to 38.8°C, can reduce the heat losses of healthy full-term infants. In addition, such care helps newborns to maintain higher body temperatures after the procedure (15) .…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the duration of the bath, the procedure is recommended to be as fast as possible, lasting from five to ten minutes. Limiting the bath to five minutes prevents stress from cold and reduces the exposure time of neonates to cleaning agents (13,15) .…”
Section: Discussionmentioning
confidence: 99%